Analisis Karakteristik Biokimia serta Pertumbuhan Spirulina platensis pada Campuran Limbah Cair Keju dan Media Zarrouk’s dengan Konsentrasi Berbeda - Apriastini, Marsiti; Agustini, Ni Wayan Sri (LPPM Universitas Terbuka, 2024)
Spirulina platensis is a filamentous, photosynthetic, multicellular blue-green microalga that thrives in various ecosystems. In addition to using Zarrouk's medium for the cultivation of S. platensis, wastewater can also serve as an alternative medium, as it contains nutrients such as nitrogen, phosphorus, and essential micronutrients for microalgal growth. The growth conditions of S. platensis are influenced by light, oxygen, and the pH of the medium. The aim of this study was to observe the growth and nutrient content of Spirulina platensis when cultivated in alternative growth media containing cheese liquid waste. This study utilized 15% cheese liquid waste in each treatment. The research involved several stages, including the cultivation of S. platensis to determine the growth pattern by measuring optical density (OD), protein content analysis using the Biuret method, and carbohydrate content analysis using the phenol-sulfuric acid method. The results showed that the lag phase of S. platensis growth occurred on day 2, during which the cells were still adapting to the wastewater. The exponential phase was observed on day 4, characterized by rapid and significant cell growth and development. In this phase, nutrients were sufficient to meet the needs of S. platensis cells, supported by favorable environmental factors. The highest protein and phycocyanin contents were observed in the mixture of cheese liquid waste and Zarrouk's medium at 100% concentration, while the highest carbohydrate and fat contents were observed in the mixture of cheese liquid waste and Zarrouk's medium at 50% concentration. In conclusion, the growth of S. platensis was most optimal in the mixture of cheese liquid waste and Zarrouk's medium at a 50% concentration.